DABCO‐Mediated C−O Bond Formation from Csp2‐Halogen Bond‐Containing Compounds and Alkyl Alcohols. Issue 12 (8th October 2018) - Wu, Han‐Qing; Luo, Shi‐He; Cao, Liang; Shi, Hao‐Nan; Wang, Bo‐Wen; Wang, Zhao‐Yang
Abstract: An efficient protocol for C−O bond formation from Csp2 −X (X=Br, Cl) bond‐containing compounds and alkyl alcohols in the presence of 1, 4‐diazabicyclo[2.2.2]octane (DABCO) as catalyst and base under mild conditions is described. The densely functionalized 2(5 H )‐furanone products can be generally obtained in moderate to excellent yields via a metal‐free protocol at room temperature without added solvent. Abstract : Killing two birds with one stone : A C−O bond formation reaction at room temperature in moderate to excellent yields is described. The reaction uses DABCO as both the base and catalyst.